2023
DOI: 10.3390/plants12030644
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Propagation of Three Date Palm (Phoenix dactylifera L.) Varieties Using Immature Female Inflorescences

Abstract: Immature female inflorescences are promising materials for use as explants for the tissue culture of date palm. Four types of MS media were used in this study during the four micropropagation stages—starting media (SM), maturation media (MM), multiplication media (PM) and rooting media (RM)—to micropropagate three elite date palm varieties, Amri, Magdoul and Barhy using the immature female inflorescences as explant. The highest percentage of callus induction in all the varieties studied was obtained on the SM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Significant changes in proliferation capacity were found between S2 and S1 (p = 0.0016), S3 and S1 (p = 0.0007), and S4 and S1 (p = 0.0002). Several investigations have demonstrated that there are significant differences in the ability to initiate morphogenesis processes both between the different formulations of culture media and between the biotypes studied [39][40][41][42]. The biotype had a significant impact on the rate of initiation.…”
Section: Resultsmentioning
confidence: 99%
“…Significant changes in proliferation capacity were found between S2 and S1 (p = 0.0016), S3 and S1 (p = 0.0007), and S4 and S1 (p = 0.0002). Several investigations have demonstrated that there are significant differences in the ability to initiate morphogenesis processes both between the different formulations of culture media and between the biotypes studied [39][40][41][42]. The biotype had a significant impact on the rate of initiation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more studies are encouraged to determine the related threshold concentration. The importance of cytokinin is not limited to daylily micropropagation as its application has significantly promoted in vitro multiplication [36,37]. In the rooting stage, the number of roots and root length were better at the low NAA concentration (0.5 mg/l) than at the higher NAA concentrations indicating that daylily tissues may contain a high quantity of auxins.…”
Section: Discussionmentioning
confidence: 99%
“…The use of seeds leads to a high degree of genetic variation and a long juvenile period before fruiting, making it difficult to maintain desirable traits of the parent tree. To overcome these limitations, micropropagation techniques have been developed as an alternative means of propagating date palms (Mazri et al, 2019;Alansi et al, 2020;Abdelghaffar et al, 2023;Solangi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%